Assessing and measuring statistics cognition in higher education online environments emerging research and opportunities - Chase, Justin P. 1987-; Yan, Zheng 1972- (IGI Global, Disseminator of Knowledge, 2017)
"This book explores the fundamental understanding of learning statistics efficiently and effectively has a lot to do with how students think about statistics, how statistical cognitive processes influence student learning, what type of environments are conducive to developing statistics cognition, when emotions, moods, and attitudes can enhance or harm statistics cognition, and other topics"--
Keywords: Education, Higher / Computer-assisted instruction; Statistics / Study and teaching (Higher); Statistics / Study and teaching / Psychological aspects; Computer-assisted instruction / Psychological aspects; Statistical literacy; Cognitive learning; Educational psychology